Image guided sacroiliac joint corticosteroid injections in children: an 18-year single-center retrospective study - Racha Chamlati; Bairbre Connolly; Ronald Laxer; Jennifer Stimec; Jyoti Panwar; Shirley Tse; Prakash Muthusami; Joao Amaral; Michael Temple; Dimitri A. Parra (BMC, 2020)
Abstract Background Sacroiliitis is commonly seen in enthesitis-related arthritis (ERA), a subtype of juvenile idiopathic arthritis (JIA). Sacroiliitis is characterized by the inflammation of the sacroiliac (SI) joints (+/− adjacent tissues). The treatment options include systemic therapy with or without corticosteroid SI joint injections. Image guided SI joint injections are frequently requested in pediatric patients with sacroiliitis. The purpose of this study was to evaluate the feasibility and efficacy of SI joint injections in children with sacroiliitis. Methods A retrospective study of patients referred to Interventional Radiology (IR) for SI joint corticosteroid injections (2000-2018). Clinical information was collected from Electronic Patient Charts and procedural details from PACS. Efficacy was determined clinically, by MRI, or both when available. Results 50 patients (13.8 years; M:F = 35:15) underwent image-guided SI joint corticosteroid injections. Most common indications were JIA (84%) and inflammatory bowel disease (14%). 80% had bilateral injections. 80% were performed under general anesthesia and 20% under sedation. The corticosteroid of choice was triamcinolone hexacetonide in 98% of patients. Needle guidance and confirmation was performed using CT and fluoroscopy (54%), Cone Beam CT (CBCT, 46%), with initial ultrasound assistance in 34%. All procedures were technically successful without any complications. 32/50 patients had long-term follow-up (2 years); 21/32 (66%) had clinical improvement within 3-months. Of 15 patients who had both pre- and post-procedure MRIs, 93% showed short-term improvement. At 2 years, 6% of patients were in remission, 44% continued the same treatment and 47% escalated treatment. Conclusion Image-guided SI joint injections are safe and technically feasible in children. Imaging modalities for guidance have evolved, with CBCT being the current first choice. Most patients showed short-term clinical and imaging improvement, requiring long-term maintenance or escalation of medical treatment.